HUBUNGAN PENGETAHUAN DIABETES MELITUS DAN PENGETAHUAN ASUPAN GIZI PADA REMAJA DI SMK X SIDOARJO - Aristia, Bella Fevi; P, Aulia Rachma; Intan, Firda; K, Yunita Dyah (Jurnal Riset Kefarmasian Indonesia, 2024)
The prevalence of diabetes mellitus (DM) in the world and nationally continues to increase. DM generally occurs in the age group >50 years; however, DM currently affects many young age groups. Adolescents affected by DM can continue to increase if they do not have good knowledge about DM and nutritional intake. This study aims to determine the level of DM knowledge and nutritional intake among high school adolescents in SMK X West Sidoarjo. This research method is descriptive-observational with prospective data collection. The research instrument used the DKQ-24 questionnaire and a valid nutritional intake questionnaire. The selected sample is in accordance with the research inclusion criteria, totaling 50 people The results showed that 76% did not know the causes of DM and diet rules; 78% people also did not know the importance of DM treatment to control blood sugar. Regarding knowledge of nutritional intake, most respondents (56%) did not know the calculation and value of BMI, 46% did not know the importance of fiber for controlling blood sugar, and 40% did not know the types of foods with a high glycemic index. The majority of respondents have good knowledge about diabetes (76%) and nutritional intake (70%). Chi-square analysis shows that there is a relationship between knowledge of DM and knowledge of nutritional intake, with a p value of 0.027. DM knowledge and nutritional intake are important to shape healthy lifestyle behaviors in an effort to prevent DM in adolescents